Analysis of Factors Influencing the Spread of Tuberculosis in West Java Province Using Poisson, Negative Binomial, and Gamma Regression Models - Mona Aprilliani Wijaya (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
Tuberculosis (TB) remains a major public health challenge in Indonesia, with West Java Province recording the highest number of cases in 2024, accounting for approximately 20% of the national total, driven by socio-economic and environmental factors. This study aims to analyze these factors influencing the spread of TB in West Java districts/cities using Poisson, Negative Binomial, and Gamma regression models. The cross-sectional quantitative design utilized secondary data from 27 districts/cities out of a total of 35, after eliminating multicollinear variables through the VIF test. Instruments consisted of 2024 BPS and Health Office reports, analyzed using descriptive statistics, Pearson correlation, overdispersion test, and GLM in RStudio 4.4.2, selecting the best model based on the smallest AIC. The results showed overdispersion (mean 16,057 cases, variance 1.71×10^9), with optimal Negative Binomial: poverty, young smokers, and malnutrition had a positive effect on TB cases, while literacy, access to clean water, and BPJS coverage significantly reduced them. The conclusion states that targeted interventions on socio-economic vulnerability provide an evidence-based strategy for the 2030 TB-Free West Java target.